Non-cirrhotic hyperammonemia in a newly diagnosed diabetic patient presenting in diabetic ketoacidosis - Manappallil, Robin George; Kumar, Pradeep; Josephine, Blessy (Indian Journal of Case Reports, 2019)
Hyperammonemia, a known cause of encephalopathy, is commonly seen in patients with liver disease. Non-cirrhotic hyperammonemia is an uncommon condition. Patients with uncontrolled diabetes can have elevated levels of ammonia. Diabetic ketoacidosis is a life threatening complication in diabetes. This is a case of a middle-aged male who presented in encephalopathy. He was found to have diabetic ketoacidosis with hyperammonemia. Encephalopathy as a result of hyperammonemia in diabetes mellitus is a rare scenario.